Assessing the influence of laterite soil mining on land use and land cover change in sub-Saharan Africa: The case of northern Ghana - Eleanor A. Dunee; Laura Atuah; Bernard N. Baatuuwie; Irene Idun (Center for Science and Technology, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Laterite soil is essential in the construction industry, especially in road and building construction. The practice of abandoning borrow pits after mining laterite soil in the Northern Region of Ghana has resulted in land degradation, as well as loss of vegetative cover and biodiversity. This study assessed the land cover (LC) changes in Northern Ghana from 2002 to 2022 to highlight how laterite soil mining has altered the Guinea Savannah Landscape. Landsat images for three selected years (2002, 2012, and 2022) were analysed using SEPAL, ArcGIS, and QGIS. The images were classified into eight LC classes: woodland, shrub/grassland, cropland, bare land, built-up, laterite (gravel) pit, floodplain, and water bodies. It was found that borrow pits increased by 16.61 km2 over the two decades. Croplands and Shrub/grasslands were identified as the most affected classes, with direct LC losses of 11.38 km2 and 7.16 km2, respectively. Additional indirect losses were attributed to agricultural expansion due to the reduction in cropland areas. It is concluded that laterite soil mining, driven by urbanisation, has a dire impact on vegetation cover and local livelihoods due to unsustainable mining practices. It is recommended that development control managers utilise the findings of this study to devise strategies for managing laterite soil mining and promoting sustainable mining practices to meet the targets of SGD 15.